Seasonal Variation of Physicochemical and Microbial Parameters of water of Nal-Damayanti Sagar Dam, Morshi, Dist. Amravati, MS, India - Ghaware AU; Jadhao RG (International Journal of Life Sciences, 2015)
This study was aimed to estimate current status of Physico-chemical characteristics and level of pollution indicator bacteria and their variation at whole stretch of dam. Some environmental parameters such as Temperature, pH, Turbidity, Dissolved oxygen, Sulphates and Nitrates were monitored. In addition, the microbial analyses involved total viable bacterial and fungal counts. The results of physicochemical parameters showed varied value; from conclusions revealed that large number of sewage drains in Morshi and agricultural discharge is mainly responsible for pollution in Nal-Damyanti Sagar Dam.